Subcutaneous seeding following surgical excision of an intracranial meningioma in a cat - Deutschland, Martin; Hoppe, Judith; Gruber, Achim D. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Traditionally patient owners express their concerns that surgical or diagnostic procedures on a tumor may induce metastasis. In pets, this has been documented in only very rare occasions, e. g. needle path metastases after diagnostic fine needle biopsies of urinary bladder or prostatic tumors. Here, we describe a case of subcutaneous seeding of a feline intracranial grade 1 meningioma 6 months after surgical resection. A 10-year-old male neutered domestic shorthaired cat with typical neurological signs was diagnosed with an extra-axial contrast enhancing mass in the dorsal frontotemporal lobes using magnetic resonance imaging (MRI). Transfronto-parietal bone craniotomy was performed and the 24 × 19 × 22 mm large tumor was largely removed. Tumor recurrence after 12 months resulted in a second surgical tumor removal. In addition, 2 subcutaneous masses of 10 × 4 × 4 mm in size were removed at the site of the original surgical site which were fully separated from the recurring meningeal tumor by the intact frontal bone. Histology and immunohistochemistry suggested the same tumor growth in all 4 masses. Most likely the tumor seeding had been caused during the first surgery. After all, the risk of surgical seeding of a benign tumor seems very low.
Keywords: Magnetic resonance imaging; brain tumor; oncology; recurrence; tumor spread